Play in the Grade One Classroom: An Exploration of Teacher Beliefs, Classroom Organization, and Obstacles to Implementation in Quebec - Amanda Quance; Joanne S. Lehrer; Helen Stathopoulos (Canadian Society for Studies in Education, 2008)
A mixed methods investigation into Grade One teachers' beliefs and practices about play in the classroom was conducted in a French public school board in Quebec. Forty-three teachers completed questionnaires, while a subset of 10 classrooms were photographed, and open-ended interviews were conducted with 7 teachers. Correlation between beliefs, practices, and experience teaching showed that 'learning through play' was positively associated with belief in 'educational toys and manipulation' (rs = 0.313, p < 0.05), and greater frequency of teacher self reported play activities (r = 0.524, p < 0.01). Teachers who had more experience teaching Grade One, believed less in 'learning through play' (r = -0.341, p < 0.05) and reported using fewer play practices in their classes (r = 0.365, p < 0.05). Total years teaching was also negatively correlated with belief in 'learning through play' (r = -0.410, p < 0.01). Photographs revealed minimal variation between classrooms, with some elements of play in half of the classrooms. Interviews revealed that teachers found play to be an effective learning strategy, that they primarily used games as play activities in their classrooms, and that school personnel and personal experience supported their use of play, while lack of time, budget and materials limited the amount of play activities implemented.